Converting Solid waste to electrical energy: review the utilization of the techniques and applications in the Region - Ghada S.mohammed; Riyam M.Alsammarraie; Sura abdulkareem salih (Journal of Madenat Alelem University College, 2024)
The MENA (Middle East & North Africa) face significant challenges in waste management due to rapid urbanization, population growth, and economic development, these challenges require innovative and sustainable solutions to deal with the increasing quantities of solid waste. Converting solid waste to electrical energy represents a promising solution that can reduce the environmental impact and provide an alternative source of energy. This study aims to review the application of different solid waste to electrical energy technologies in the MENA, focusing on incineration, gasification, anaerobic digestion, landfill gas recovery, and hybrid systems. Also, it presents environmental, economic, and social advantages, as well as their Challenges. This study also presents an analysis of the regional waste composition, the suitability of the technologies, and the Regulatory Barriers to Solid Waste to Electrical Energy Technologies with identifying potential opportunities to enhance the application of these technologies. Also, this study provides strategic recommendations to support the adoption of Solid waste to electrical energy technologies in the MENA, including improving regulatory frameworks, providing financial incentives, and enhancing public-private partnerships. The study also calls for increasing public awareness and waste source segregation to maximise these technologies' benefits. Through these recommendations, Solid waste to electrical energy technologies can contribute to achieving sustainable development goals and promoting a circular economy in the region, thus improving quality of life and reducing environmental pollution.